Synthesis and Spectroscopic Investigation of New Complexes of [8– (2– carboxyphenylazo) –6– formyl –7– hydroxy –5– methoxy –2– methylchromone with La (III) and Th (IV)] - El-Agaili, M. M.; EL-Maihoub, A. A. (Al-Mukhtar Journal of Sciences, 2000)
New complexes of La (III) and Th (IV) ions with 8– (2– carboxyphenylazo) –6– formyl –7– hydroxy –5– methoxy –2– methylchromone (L) have been synthesized and investigated by elemental analysis and IR. Spectroscopy. The complexes of the general chemical formula ML2Xm . nH2O, where M; La (III) and Th (IV), X = OH– or H2O, m = 1 – 2, n = 6 or 8 and L = ligand have been synthesized. The IR spectra indicate that the complication occurs through the aldehydic group in position six and hydroxyl group in position seven, while the position of CO2H and N = N groups did not change during the complexation. The molar conductance indicate that the prepared complexes are non–electrolytic.